SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN STARTING LINE-UP PEMAIN SEPAKBOLA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DAN ANALISIS ASOSIASI ( STUDI KASUS : PERSIK KEDIRI ) - , andika kurnia adi pradana ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Decision Support System is one part of the Computer-Based Information System which is an interactive computer information system that can provide alternative solutions for decision makers. For example, a football coach, in determining the starting line-up players in accordance with the conditions and the ability of players and formations that have been set requiring a decision support system to assist in making decisions more quickly, carefully and avoid subjective decisions are produced. For that built a Decision Support System that aims to help coachâs job in deciding who has the right players into the starting line-up through the selection process using a Model Analytical Hierarchy Process (AHP) and Association Analysis. AHP model is a functional hierarchical model with the main input is the human perception. This model has ability to solve multicriteria problems based on comparison of preferences of each element in the hierarchy. From this AHP model will be generated the ranking of players for each position. Association analysis is a method to find the associative rules between a combination of items. In associative rules will get the couple of players from the players who occupy the highest position in the ranking of players. Determination of the starting line-up is using a combination of the ranking of players and associative rules to a predefined distribution pattern. From the test results indicate Decision Support System For Determining The Starting Line-Up Football Player Using Analytical Hierarchy Process Method And Analysis Association (Case Study: Persik Kediri) can help the job of Persik Kediri coach in deciding who has the right players into the starting line-up with faster, more accurate and effective.